Blood Profile in Normal One Humped Dromedary (Camelus Dromedarius) Camels in Libya. Part 4: Effect of Age Variation on Biochemical and Haematological Blood Profile - Anwar Abdalmula; Mansur Shmela; Fahima Alnagar; Amal Buker; Fathi Benashour; Ismail Abograra (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. As little is known about the blood profile of camels in Libya, this article is the last of a four-part series describing the biochemical and hematological blood profile in Libyan camels. In part one of these manuscripts, the overall blood biochemical and hematological mean values of camels in Libya were determined. Parts two and three evaluated the effects of breed and gender on these values respectively. In this forth and last part, the effect of age was examined. Methods. Blood samples were collected from eight young and fifty-eight adult apparently healthy camels and the levels of enzymes, metabolites, electrolytes and hematological indices were measured. Results. The blood of the young camels showed higher values of glucose, urea, triglycerides, total cholesterol, Low Density Lipoprotein (LDL), Very Low Density Lipoprotein (VLDL), Sodium (Na), Potassium (K), Phosphorus (Ph), Calcium (Ca) than the adult camels which on the other hand showed higher values of Alkaline Phosphatase (ALP), Lactate Dehydrogenase (LDH), High Density Lipoprotein (HDL) and Magnesium (Mg). Conclusion. This study has shown significant age differences between young and adult Libyan camels in many biochemical but not hematological parameters.